2017
DOI: 10.1002/bkcs.11145
|View full text |Cite
|
Sign up to set email alerts
|

OH+ Isoprene: A Direct Dynamics Study

Abstract: The products and mechanisms active in the isoprene + OH reaction were investigated using the direct dynamics method. High energies were used in order to identify every possible reaction channel. The trajectories were classified as dissociative and nondissociative, depending on whether fragmentation occurred during the 4 ps time window of the simulations. The nondissociative trajectories were further classified as radical additions, rearrangements, and cyclizations. The most dominant category was the addition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
(97 reference statements)
0
5
0
Order By: Relevance
“…Using computational approaches, addition of OH to the tertiary and secondary carbon centers of isoprene have been estimated to be 4–8% of the total OH reactivity. There is, however, little laboratory evidence to provide any constraint on these branching fractions . If these channels are as significant as calculated, then describing their products is essential.…”
Section: The Challenges That Remainmentioning
confidence: 99%
See 1 more Smart Citation
“…Using computational approaches, addition of OH to the tertiary and secondary carbon centers of isoprene have been estimated to be 4–8% of the total OH reactivity. There is, however, little laboratory evidence to provide any constraint on these branching fractions . If these channels are as significant as calculated, then describing their products is essential.…”
Section: The Challenges That Remainmentioning
confidence: 99%
“…Despite the allylic resonance, abstraction of the methyl hydrogen is likely less than 1% of the total reaction under atmospheric conditions (cf. recent calculations on propene 96 and isoprene 97 ).…”
Section: Location Of Oh Additionmentioning
confidence: 99%
“…Therefore, in principle, the reaction of isoprene with • OH, NO 3 , O 3 , and • Cl can proceed via both H-abstraction and addition pathways. It has previously been shown that the addition pathway is exclusive for reactions of isoprene with NO 3 and O 3 . ,,, The addition pathway is also the major reaction route for the • OH + isoprene reaction, where H-abstraction from the −CH 3 group to form allylic radicals only plays a minor role (≤1%). ,, However, the H-abstraction pathway has a significantly higher contribution to the removal of isoprene (13–17%) in the reaction of • Cl with isoprene, , compared with the reactions of isoprene with • OH, NO 3 , and O 3 . In some locations such as North China Plains or coastal regions, the concentration of • Cl can reach 10% of that of • OH. , This implies that the H-abstraction pathway can contribute up to 3.6–4.9% (see the SI) to the total removal of isoprene at daytime even though the only contribution of • Cl on H-abstraction is considered.…”
Section: Introductionmentioning
confidence: 99%
“…7,10,15,16 The addition pathway is also the major reaction route for the • OH + isoprene reaction, where H-abstraction from the −CH 3 group to form allylic radicals only plays a minor role (≤1%). 7,17,18 However, the Habstraction pathway has a significantly higher contribution to the removal of isoprene (13−17%) in the reaction of • Cl with isoprene, 4,19−23 compared with the reactions of isoprene with • OH, NO 3 , and O 3 . In some locations such as North China Plains or coastal regions, the concentration of • Cl can reach 10% of that of • OH.…”
mentioning
confidence: 99%
“…Oxidation of isoprene by the hydroxyl radical, the latter of which is often referred to as a detergent of the atmosphere because it is the primary agent for removal of atmospheric volatile organic compounds (VOCs), initiates a series of reactions that results in tropospheric ozone formation and • OH propagation. The oxidation of isoprene in particular involves • OH addition to one of the four sp 2 hybridized carbon centers along the butadiene backbone. , Hydrogen (H) abstraction by • OH is a higher barrier reaction than OH–VOC adduct formation for unsaturated VOCs, though abstraction pathways have been suggested for several substituted allylic species to occur from nearly atmospheric to combustion-like temperatures, as well as very low pressures. …”
Section: Introductionmentioning
confidence: 99%